( lo g 2 3 ) ( lo g 3 4 ) ( lo g 4 5 ) ( lo g 5 6 ) ⋯ ( lo g 5 1 1 5 1 2 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yes. This is just a telescoping product is disguise.
Same Method.
Let the given expression equal x . Then since a lo g a ( b ) = b we have that
2 x = ( 2 lo g 2 ( 3 ) ) ( lo g 3 ( 4 ) ) ( lo g 4 ( 5 ) ) . . . . ( lo g 5 1 1 ( 5 1 2 ) ) =
( 3 lo g 3 ( 4 ) ) ( lo g 4 ( 5 ) ) ( lo g 5 ( 6 ) ) . . . . ( lo g 5 1 1 ( 5 1 2 ) ) =
( 4 lo g 4 ( 5 ) ) ( lo g 5 ( 6 ) ) ( lo g 6 ( 7 ) ) . . . . ( lo g 5 1 1 ( 5 1 2 ) )
and so on, creating a "domino effect" which leaves us with
2 x = 5 1 1 lo g 5 1 1 ( 5 1 2 ) = 5 1 2 ⟹ x = 9 .
Very unusual and creative! This reminds me of induction for some reason.
Beautiful!
The property used here is log b to the base a can be written as (log b)/(log a).
So, log 3 to the base 2 is (log 3)/(log 2).
All the terms cancel in this telescopic multiplication and the remaining terms are log(512)/log(2),
Also, log(a^b) = b x log(a).
512 = 2^9.
So, 9 log(2)/log(2) = 9.
Problem Loading...
Note Loading...
Set Loading...
( lo g 2 3 ) ( lo g 3 4 ) ( lo g 4 5 ) ( lo g 5 6 ) . . . ( lo g 5 1 1 5 1 2 ) = ( lo g 2 lo g 3 ) ( lo g 3 lo g 4 ) ( lo g 4 lo g 5 ) ( lo g 5 lo g 6 ) . . . ( lo g 5 1 1 lo g 5 1 2 ) = ( lo g 2 lo g 5 1 2 ) = ( lo g 2 lo g 2 9 ) = ( lo g 2 9 lo g 2 ) = 9